2012
DOI: 10.5267/j.msl.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on empowering private bank workers using EFQM

Abstract: Empowering workers play an essential role on increasing productivity in any organization. The service industries such as insurance companies or banks mostly rely on their own people to retain their customers and incomes. The recent increasing trend on the number of private banks in Iran has increased competition among existing banks. The banking industry strives to empower its employees as much as possible in an attempt to maintain market share by not losing its customers. In this paper, we present an empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The results of investigations of application of the elements of TQM practice, or excellence model criteria on business results, or satisfaction and loyalty of employees rarely occur in the literature, although they should present fundamentals for good performance of each bank (Al-Shobaki et al, 2010;Beikzard et al, 2012;Spasojević-Brkić & Putnik., 2013;Marimon et al, 2012). Therefore, in this paper, the focus of the research is directed toward defining the model of impact by implementing the criteria of the EFQM excellence model on the loyalty and satisfaction of the employees working in banks in Serbia.…”
mentioning
confidence: 99%
“…The results of investigations of application of the elements of TQM practice, or excellence model criteria on business results, or satisfaction and loyalty of employees rarely occur in the literature, although they should present fundamentals for good performance of each bank (Al-Shobaki et al, 2010;Beikzard et al, 2012;Spasojević-Brkić & Putnik., 2013;Marimon et al, 2012). Therefore, in this paper, the focus of the research is directed toward defining the model of impact by implementing the criteria of the EFQM excellence model on the loyalty and satisfaction of the employees working in banks in Serbia.…”
mentioning
confidence: 99%
“…Abbasi and Farhangi (2013) used EFQM method for broadcasting firm in Iran. Beikzad et al (2012) performed an empirical study on empowering private bank workers using EFQM. Kazemi et al (2012) presented a framework for organizational excellence to detect any possible problems in home appliances industry.…”
Section: Introductionmentioning
confidence: 99%
“…Iravani (2012) performed a survey on empowering single mothers and reported that audacity and social responsibility were the most important items while being optimistic, independent and flexibility were counted as having the least impact on empowering single mothers. Beikzad et al (2012) presented an empirical investigation to detect the most important factors empowering bank employees. The results indicated that leadership, academic qualification, appropriate policy and strategy, cooperation and processes played important role on empowering and enabling banks' employees.…”
Section: Introductionmentioning
confidence: 99%